Reviewing the past responding to new challenges : - Martin, Frederic (Thanh nien, 2009)
Since the launch of ‘Doi Moi’ reforms in 1986, Viet Nam has embarked upon a hugely successful process of structural reform and socio-economic development. The economy has been fundamentally transformed, from a centrally planned command economy model, to a market based one rapidly integrating into the wider global economy. Poverty has been reduced from approximately 58% of the population in 1993, to only 16% in 2006 (using GSO’s international poverty line data) with other non-income based indicators of welfare such as access to basic social services and infrastructure confi rming this positive trend. Throughout this period, the Government has continued to invest signifi cant resources in national poverty reduction programmes with the objective of promoting broad based development and social harmony.